2022
DOI: 10.1017/wet.2022.24
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resistance of silky windgrass to acetolactate synthase- and acetyl-CoA synthase–inhibiting herbicides

Abstract: Field and pot experiments were conducted in Greece to study the occurrence of resistance in silky windgrass to acetolactate synthase (ALS)- and acetyl-CoA synthase (ACCase)-inhibiting herbicides. Twenty-four populations of silky windgrass were examined in whole-plant response experiments. High levels of field-evolved resistance to chlorsulfuron (0 to 28% control in terms of fresh weight reduction) with the recommended field rates were confirmed in most silky windgrass populations. However, other ALS inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, repeated use of similar herbicidal modes of action (MOAs) and the associated selection pressure have led to the evolution of herbicide resistance in varieties of economically important weedy species such as Alopecurus myosuroides ( Lan et al., 2022 ; Goldberg-Cavalleri et al., 2023 ), Amaranthus palmeri ( Manicardi et al., 2023 ), Apera spica venti ( Košnarová et al., 2021 ; Papapanagiotou et al., 2022 ), Bromus sterilis ( Sen et al., 2021 ), Lolium spp ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Zhu et al., 2023 ). Recent studies showed that the majority of these weeds were also developing multiple resistances against herbicides with more than one mode of action ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Košnarová et al., 2021 ; Lan et al., 2022 ; Papapanagiotou et al., 2022 ; Zhu et al., 2023 ). From a molecular point of view, herbicide resistance mechanisms might be categorized into target-site based resistance (TSR) and non-target-site based resistance (NTSR) ( Torra and Alcántara-de la Cruz, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, repeated use of similar herbicidal modes of action (MOAs) and the associated selection pressure have led to the evolution of herbicide resistance in varieties of economically important weedy species such as Alopecurus myosuroides ( Lan et al., 2022 ; Goldberg-Cavalleri et al., 2023 ), Amaranthus palmeri ( Manicardi et al., 2023 ), Apera spica venti ( Košnarová et al., 2021 ; Papapanagiotou et al., 2022 ), Bromus sterilis ( Sen et al., 2021 ), Lolium spp ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Zhu et al., 2023 ). Recent studies showed that the majority of these weeds were also developing multiple resistances against herbicides with more than one mode of action ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Košnarová et al., 2021 ; Lan et al., 2022 ; Papapanagiotou et al., 2022 ; Zhu et al., 2023 ). From a molecular point of view, herbicide resistance mechanisms might be categorized into target-site based resistance (TSR) and non-target-site based resistance (NTSR) ( Torra and Alcántara-de la Cruz, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides have been used to control weeds and increase the quality and quantity of major crops since their discovery. However, repeated use of similar herbicidal modes of action (MOAs) and the associated selection pressure have led to the evolution of herbicide resistance in varieties of economically important weedy species such as Alopecurus myosuroides (Lan et al, 2022;Goldberg-Cavalleri et al, 2023), Amaranthus palmeri (Manicardi et al, 2023), Apera spica venti (Kosňarováet al, 2021;Papapanagiotou et al, 2022), Bromus sterilis (Sen et al, 2021), Lolium spp (Tehranchian et al, 2019;Ma et al, 2020;Zhu et al, 2023). Recent studies showed that the majority of these weeds were also developing multiple resistances against herbicides with more than one mode of action (Tehranchian et al, 2019;Ma et al, 2020;Kosňarováet al, 2021;Lan et al, 2022;Papapanagiotou et al, 2022;Zhu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%